2005
DOI: 10.1093/rheumatology/kei245
|View full text |Cite
|
Sign up to set email alerts
|

Post-interventional immunosuppressive treatment and vascular restenosis in Takayasu's arteritis

Abstract: Restenosis occurred in 31.7% of TA patients after intervention. A lower restenosis rate was observed when the vascular interventions were performed at the stable stage and when post-interventional immunosuppressive treatment was implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 34 publications
2
60
0
5
Order By: Relevance
“…Percutaneous transluminal angioplasty/ stenting has been reported to have a higher restenosis rate in the Indian cohort compared with the other reports (12%-71.4%) (26,28). The restenosis rate was reduced when surgical treatment was performed during the inactive stage of the disease and under treatment with both glucocorticoids and immunosuppressive (IS) agents (29)(30)(31). These data suggest that early immunosuppression and choice of treatment may be influencing the different rates of outcome in the literature.…”
Section: Prognosismentioning
confidence: 84%
“…Percutaneous transluminal angioplasty/ stenting has been reported to have a higher restenosis rate in the Indian cohort compared with the other reports (12%-71.4%) (26,28). The restenosis rate was reduced when surgical treatment was performed during the inactive stage of the disease and under treatment with both glucocorticoids and immunosuppressive (IS) agents (29)(30)(31). These data suggest that early immunosuppression and choice of treatment may be influencing the different rates of outcome in the literature.…”
Section: Prognosismentioning
confidence: 84%
“…First, selecting the timing of the procedure: PTA and stent implantation should not be performed at the stage of active inflammation. Pack et al 17 observed that the restenosis rate was lower when vascular interventions were performed at the stable stage of TA. Second, selecting proper balloon and stent: balloon inflation at high pressure is required for rigid stenotic lesions in pulmonary arteritis.…”
Section: Discussionmentioning
confidence: 99%
“…O acompanhamento pós-operatório desses pacientes deve ser com consultas de rotina, monitoramento da pressão arterial, provas de atividade inflamatória e exames de imagens da aorta e seus ramos para diagnosticar novas lesões estenóticas passíveis de tratamento, já que mesmo com a doença controlada clinicamente as lesões arteriais podem continuar progredindo e sendo necessário outras intervenções 1,3,5,6,14 .…”
Section: Discussionunclassified